Indian middle classes : their growth in modern times - Misra, B. B. (London, 1961)
The subject of the rise of the Indian middle classes, obviously one of the most important developments in modern India, has never previously been ex plored. Dr Misra modestly described his work as a 'mere introductory survey', but in fact he has undertaken a very thorough study extending from Mughal times to the present day and drawing on much research material to be found nowhere else. In it he traces the development of the Indian middle classes in the spheres of land and the professions, trade, and industry, and examines their character and historical roles against the background of British rule in India.
Keywords: Middle classes-India